Evaluation of Cluster Management Quality Based on Consumer Opinion Sentiment Analysis - Młodzianowski Piotr; Valencia Hernandez Jose Aldo (Foundations of Management, 2021)
This article discusses the issue of assessing the quality of cluster management by utilizing Internet customer feedback about companies that are members of clusters. Due to the growing number of Internet users, companies pay greater attention to the opinions published about them. Consumers are also increasingly willing to share their opinions and thoughts about the products they use. As a result, it has become possible to analyze the quality of services and products provided by an enterprise based on Internet opinions. In this article, we analyze the quality of cluster management as reflected in the European Cluster Excellence Initiative (ECEI) label, as measured by sentiment analysis of Internet opinions. The paper proposes a method for the identification and evaluation of Internet sources used in the opinion sentiment analysis. Sentiment analysis of Internet opinions of cluster and in-cluster business customers was performed, and the results were compared with the level of the ECEI label, which was awarded to the analyzed clusters. The conducted research showed convergences between formalized systems of management quality assessment and the level of opinions expressed on the Internet. The results testify that sentiment analysis can complement the evaluation of cluster management quality.